CULTURAL HERITAGE’S MANAGEMENT: A COMPARATIVE STUDY OF THAILAND AND VIETNAM - Polcharoen, Chanikan (Academic Journal Phranakhon Rajabhat University, 2024)
This research aims to 1) study the management of cultural heritage in Thailand and Vietnam and 2) compare the management practices of cultural heritage in both countries. The methodology is qualitative research, with data collected from documentary reviews and semi-structured interviews with five key informants. The results show that the management of cultural heritage sites in the two countries differs significantly due to their unique civilizations and varying management policies. Thailand's civilization, influenced by India and the Khmer Empire, developed into distinct national Thai arts and culture. Cultural heritage in Thailand is closely tied to elite groups, particularly Buddhist temples, which were often built by the monarchy and dominated the cultural heritage landscape. The Fine Arts Department is the responsible institution for cultural heritage governance. Buddhist temples have become critical assets in the tourism industry, with local communities benefiting from the commodification of these sites. In contrast, Vietnam's historical development was heavily influenced by China for much of its history. The Socialist Republic of Vietnam's government holds the authority to register community cultural heritage under policies of "Folklorization" and "Exoticization." The Vietnamese government has successfully secured funding for restoration projects from European countries and UNESCO. However, Vietnam also has Cham castles from the ancient Champa kingdom, one of the oldest civilizations in Southeast Asia. A challenge remains, as the Cham ethnic group is a minority, and many Vietnamese people are not well-acquainted with Cham castles. If the Vietnamese government provides more support for preserving Cham castles, and if the Thai government can balance the benefits among various ancient sites, managing cultural heritage in both countries could achieve greater success and sustainable development for local communities.